The internal rotation and shift-test for the detection of superior lesions of the rotator cuff: reliability and clinical performance - Georg, Fieseler (2022)
BackgroundUsing reliable and valid clinical tests are essential for proper diagnosis and clinical outcomes among injuries involving the rotator cuff. The addition of a new clinical examination test could improve the clinical diagnosis and informative value of the sensitivity and specificity of pathology. This study of diagnostic accuracy evaluated the use of a new rotator cuff test, called the internal rotation and shift-test (IRO/shift-test), to determine its reliability and clinical performance (sensitivity, specificity, positive (PPV)/negative predictive value (NPV)). Clinical diagnostic outcomes were confirmed with radiological findings (MRI). Methods100 patients from a specialized shoulder unit participated (64 male, 36 female, mean age: 55 ± 13.5 years). A single-blinded (no knowledge of prior clinical or technical diagnostics) study design was used with two experienced physicians performing the IRO/shift-test. For clinical performance, all clinical testing was compared with MRI. ResultsThe intra-rater (ICC = 0.73, 95% CI: 60-82) and inter-rater (ICC = 0.89, 95% CI: 81-94) coefficients for the IRO/shift-test showed good-to-excellent reliability. 75% of the patients showed a positive IRO/shift-test, while 65% had a radiologically diagnosed superior rotator cuff tear. 60% of these patients had both a positive IRO/shift-test and objective rotator cuff tear via MRI. The sensitivity of the IRO/shift-test to detect superior rotator cuff lesions based on MRI diagnosis was calculated at 92% (95% CI: 86-99%), while specificity was 67% (95% CI: 50-84%). Predictive values were also found to be high with 86% PPV (95% CI: 78-94%) and 80% NPV (95% CI: 64-96%). ConclusionOur results demonstrate that the IRO/shift-test is a reliable and valid tool for assessing superior rotator cuff pathology. With good-to-excellent intrarater and inter-rater reliability and strong sensitivity and specificity this test should be considered a valuable addition to clinicians’ cadre of clinical evaluation tools.